Trading Volume and Different Aspects of Disagreement Coincident with Earnings Announcements. - Bamber, Linda Smith; Barron, Ode E.; Stober, Thomas L. (The Accounting Review, 1997)
This paper investigates the association between aspects of investors' disagreement around earnings announcements and investors' trading decisions. Theory suggests that trading volume arises because of investor disagreement, but disagreement is a multi-faceted construct. We find that three distinctly different aspects of disagreement each play an incremental role in explaining trading volume around earnings announcements, even after controlling for the magnitude of the contemporaneous price change. These aspects of disagreement are: dispersion in prior beliefs, change in dispersion, and belief jumbling . Dispersion in prior beliefs is the level of variation in expectations before the earnings announcement, change in dispersion is the difference in the level of dispersion in beliefs after vs. before the earnings announcement, and belief jumbling occurs when investors' beliefs change positions relative to each other around the earnings announcement. Our results indicate that each of these three aspects of disagreement is associated with investors' real economic (i.e., trading) decisions around earnings announcements.